18-year change in serum intact fibroblast growth factor 23 from midlife to late life and risk of mortality: the ARIC Study. Issue 1 (12th May 2022) - Ishigami, Junichi; Honda, Yasuyuki; Karger, Amy B; Coresh, Josef; Selvin, Elizabeth; Lutsey, Pamela L; Matsushita, Kunihiro
Abstract: Objective: Fibroblast growth factor 23 (FGF23) concentration increases in response to declining kidney function to preserve normal phosphate concentrations. However, the etiological association of change in FGF23 concentration with mortality has not been examined in the general population. Design and methods: We analyzed 5458 participants of the Atherosclerosis Risk in Communities Study who had intact FGF23 and estimated glomerular filtration rate (eGFR) assessed during midlife (visit 3, 1993–1995, mean age: 58 years) and late life (visit 5, 2011–2013, 76 years) to examine the association of FGF23 change over 18 years from mid-life to late life with the subsequent risk of mortality in late life using Cox regression models. Results: The median 18-year change in intact FGF23 was +17.3 pg/mL. During a median follow-up of 7.2 years following visit 5, 1176 participants died. In multivariable Cox models, elevated mortality was seen in the highest quartile of FGF23 change (ΔFGF23: ≥31.3 pg/mL) (adjusted hazard ratio (aHR): 1.61 (95%CI: 1.36–1.90), or 1.37 (1.15–1.64) after additionally adjusting for eGFR change, compared with the lowest quartile (≤6.4 pg/mL)). When both FGF23 change and FGF23 in late life were simultaneously entered into the Cox model, FGF23 in late life, but not FGF23 change, was an independent predictor of mortality; however, we observed a high correlation between FGF23 change from midlife to late life and FGF23 in late life ( r  = 0.77). Conclusions: Serum intact FGF23 change from midlife to late life was associated with subsequent risk of mortality independent of decline in kidney function. Our findings further support the implications of FGF23 beyond its association with kidney function.